2017
DOI: 10.5847/wjem.j.1920-8642.2017.04.002
|View full text |Cite
|
Sign up to set email alerts
|

Rehabilitation of vulnerable groups in emergencies and disasters: A systematic review

Abstract: BACKGROUND: Natural and man-made disasters, especially those occurring in large scales not only result in human mortality, but also cause physical, psychological, and social disabilities. Providing effective rehabilitation services in time can decrease the frequency of such disabilities. The aim of the current study was to perform a systematic review related to rehabilitation of vulnerable groups in emergencies and disasters. METHODS:The systematic review was conducted according to the preferred reporting item… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 31 publications
(71 reference statements)
1
15
0
1
Order By: Relevance
“…The interventions were also effective in treating and reducing the survivors' PTSD symptoms like anxiety and depression, and also in enhancing their psychological resilience [35,36,38,39]. These findings are consistent with previous results from a broad systematic literature review and meta-analysis studies that similarly explored the different rehabilitation interventions, services and outcomes in post-earthquake settings, and those following other disasters within and outside China [2,[13][14][15]43,44,[48][49][50][51][52]. Encouragingly, some of the HRR programs after the 2008 Wenchuan earthquake, such as physical and physiological rehabilitation, commenced within the first 5 months after the earthquake, which is commendable and helped to ameliorate long-term impacts such as injuries and PTSD from turning into acute problems for survivors that would prevent them from returning to normal life.…”
Section: Discussionsupporting
confidence: 83%
See 3 more Smart Citations
“…The interventions were also effective in treating and reducing the survivors' PTSD symptoms like anxiety and depression, and also in enhancing their psychological resilience [35,36,38,39]. These findings are consistent with previous results from a broad systematic literature review and meta-analysis studies that similarly explored the different rehabilitation interventions, services and outcomes in post-earthquake settings, and those following other disasters within and outside China [2,[13][14][15]43,44,[48][49][50][51][52]. Encouragingly, some of the HRR programs after the 2008 Wenchuan earthquake, such as physical and physiological rehabilitation, commenced within the first 5 months after the earthquake, which is commendable and helped to ameliorate long-term impacts such as injuries and PTSD from turning into acute problems for survivors that would prevent them from returning to normal life.…”
Section: Discussionsupporting
confidence: 83%
“…Earthquakes, like any other disasters, are traumatic events and they result in a range of physical, mental and psychological health consequences [2,8,[12][13][14][15]43,[50][51][52]56]. Indeed, this is attested to in the results of six studies in our systematic review [35][36][37][38][39]41]-which showed a high prevalence of PTSD among the different groups of survivors of the 2008 Wenchuan earthquake.…”
Section: Discussionmentioning
confidence: 83%
See 2 more Smart Citations
“…[7] In a study on the earthquake in Lorestan Province, Iran, which was performed using a focus group discussion (FGD), it was concluded that women encountered socioeconomic needs, loss of assets, insecurity, and fertility problems. [8] A qualitative study carried out through consultation with scholars, highlighted issues including basic living and security needs, social and status development, access to facilities and values, awareness of rights, and participation in policy-making and the community for women in disasters. [9] In a group discussion with 35 experts in a qualitative study, issues like water, shelter, security, respect, suitable communication, awareness, and employment were introduced as the requirements of earthquake survivors.…”
Section: Introductionmentioning
confidence: 99%